Penurunan Stres Fisik dan Psikososial Pasien Pre Operasi Bedah Onkologi Melalui Meditasi Terapi di Salah Satu Rumah Sakit di Kota Padang : Reduction of Physical and Psychosocial Stress of Oncology Surgery Preoperative Patients Through Meditation Therapy in One of the Hospitals in Padang City - Renidayati (NERS Jurnal Keperawatan, 2016)
Generally, the patients will undergo the surgery will feel stress, both physical and psychological stress (anxiety). It is very dangerous because of the high heart rate and blood pressure will aggravate cardiovascular system. This study aimed to determine "The Decrease Of The Physical and Psychosocial Stress For Pre Onclogy Surgery Patients" at one hospital in Padang. The study used "Quasi-experimental pre-post test without control group" design with the intervention of meditation therapy. These samples included 44 people.Sampling bThese samples included 44 people.The sampling used by way purpusive sampling. The testing differences in average decline of physical and psychosocial stress in the intervention group and the control group is T test. The results showed an average decline of physical and psychosocial stress after meditation more in the intervention group compared with the control group. The conclusion significantly meditation therapy can reduce physical and psychosocial stress in patients withpreoperative oncology surgical. It needs to be applied as a therapy nursing meditation therapy in treating preoperative patients at least once a day for 30 minutes.